The Impact Of Blogging On Efl Students’ Writing Development - Muhi, Zubair Hamad (English Learning Innovation, 2023)
Weblogs, often known as "blogs" or "web logs," are currently among the most popular Internet apps. The current paper concerns the impact of blogging on the writing development of EFL students. This article also sought to understand the views of tertiary-level English language learners and examine the effects of blogging on academic writing The questionnaire survey was sent to five tertiary education universities in Iran. The data has been taken from 43 participants Six open-ended questionnaire items were measured. The method used was descriptive statistics and percentages gleaned from the data. The findings showed that students who utilized blogging in their academic writing saw a significant improvement in success scores, demonstrating that blogging helps students become better writers. Students also reported good views toward using blogs in their writing assignments, which, coupled with the results from the study, may suggest that students who have positive attitudes toward blogging are likely to develop into better writers.